Clematis maguanensis and C. pingbianensis (Ranunculaceae), another two new synonyms of C. meyeniana, a species widely distributed in eastern and southeastern Asia - Xiong, Si-Min; Huang, Qiao-Lan; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2025)
Based on careful observations of both herbarium specimens (including type material) and living plants in the wild, we demonstrate that Clematis maguanensis and C. pingbianensis (Ranunculaceae), both described from southeastern Yunnan, China, are not essentially different from C. meyeniana in any characters, a species widely distributed in eastern and southeastern Asia. The paratype collection of C. pingbianensis is determined to belong to C. armandi. We therefore place both C. maguanensis and C. pingbianensis in synonymy with C. meyeniana herein.